Tofacitinib in patients with moderate‐to‐severe chronic plaque psoriasis: long‐term safety and efficacy in an open‐label extension study. (1st October 2018) - Valenzuela, F.; Korman, N.J.; Bissonnette, R.; Bakos, N.; Tsai, T.‐F.; Harper, M.K.; Ports, W.C.; Tan, H.; Tallman, A.; Valdez, H.; Gardner, A.C.
Summary: Background: Tofacitinib is an oral Janus kinase inhibitor. Final safety and efficacy data from an open‐label extension study of tofacitinib in psoriasis are reported. Objectives: To evaluate the long‐term safety and durability of efficacy of tofacitinib in adults with moderate‐to‐severe chronic plaque psoriasis. Methods: Eligible patients who completed qualifying phase II/III tofacitinib studies received tofacitinib 10 mg twice daily (q12h) until month 3; subsequently, the dose could be adjusted by investigators to either 5 or 10 mg q12h. Adverse events (AEs) are reported up to month 66 and laboratory data up to month 54. Efficacy end points up to month 54 included Physician's Global Assessment of 'clear' or 'almost clear' (PGA response) and 75% improvement in Psoriasis Area and Severity Index (PASI 75). Results: Overall, 2867 patients received tofacitinib, with a median treatment duration of 35·6 months. Adverse events (AEs) and serious AEs were reported in 82·5% and 13·7% of patients, respectively; 13·9% of patients discontinued owing to AEs; and 29 patients died. Incidence rates (patients with event/100 patient‐years) were 1·16 for serious infections, 0·67 for malignancies and 0·26 for major adverse cardiovascular events. After initial changes in qualifying studies, most laboratory parameters were generally stable over 54 months. PGA response was achieved by 52–62% of patients and PASI 75 by 56–74% of patients at each study visit through month 54. Conclusions: In patients with psoriasis, the safety profile of tofacitinib over 66 months was similar to previous reports in phase III studies and efficacy was sustained through 54 months (NCT01163253).